The effect of dynamic assessment on Iranian EFL students’ critical reading performance - Khonamri, Fatameh; Sana’ati, Mohammad Kazemian (Penerbit Universiti Kebangsaan Malaysia, 2016)
The main purpose of this research was to investigate the impact of Dynamic Assessment-based instruction on the development of critical reading through an interventionist approach and based on quasi-experimental research design. For selection purposes, PET (Primarily English Test) was used and 61 male students were chosen out of 80 male students. 30 students were included in the experimental (DA) group and 30 students were chosen for the control (Non-DA) group. All assessment sessions and the enrichment program (EP) sessions took place within a thirteen- week period, excluding a week of break. The mediation procedures were based on the Graduated Prompt Method. Before the EP sessions, the critical reading and vocabulary sections of the new SAT were administered statically to students in both groups as a pre-test. The reading passages were selected from sample tests of SAT and also were ranked using Flesh Reading Scores based on their degree of difficulty. After having 10 EP sessions, the same test was administered dynamically as a post-test to the DA group and statically to the Non-DA group. A month later, a far transfer assessment test was administered dynamically to the DA group. The Data were analyzed through independent T-tests, a set of one –way ANOVA and Pearson Correlations. The results showed that there was a significant difference in scores for DA group post –test and Non-DA group post-test. Additionally, there was a strong correlation between DA and transfer assessment scores. It was concluded that the participants’ performance improved significantly on the DA posttest and far transfer assessment tests.